Nylon composite material as well as preparation method and application thereof
By adding zinc stannate and carbonate with a specific thermal decomposition temperature into nylon composite materials, the deficiencies in smoke density and mechanical properties of existing nylon materials are solved, and high-performance halogen-free flame-retardant nylon materials are achieved.
Patent Information
- Application Number
- CN202411542813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing halogen-free flame-retardant nylon materials cannot meet the requirements of HL2/3.0mm smoke density test, and the high proportion of magnesium hydroxide addition in the smoke inhibitor has a great impact on the mechanical properties, and it is easy to decompose crystallized water to reduce product performance.
By adding a specific mass portion of zinc stannate and carbonate with a thermal decomposition temperature of ≥480°C into the nylon composite material, the amount of zinc stannate added can be reduced, and the combustion can be reduced without damaging the mechanical properties. Smoke density during the process.
The nylon composite material can meet the HL3/3.0mm level requirements of EN45545-2:2020R22&R23 smoke density test, while maintaining excellent mechanical properties and flame retardant properties.
Smart Images

Figure BDA0005113156920000071 
Figure BDA0005113156920000072 
Figure BDA0005113156920000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a nylon composite material and a preparation method and application thereof. Background Art
[0002] Modern society is inseparable from electricity, transportation and various facilities in new energy transportation. Inevitably, the use of the above materials will lead to the risk of fire due to various factors. After a fire, a large amount of smoke is usually generated during the burning process, causing environmental pollution, destroying the rescue vision, and causing great harm to the human body; therefore, how to develop halogen-free flame retardant and low smoke density products is imminent.
[0003] At present, the smoke density of mature halogen-free flame-retardant nylon materials on the market only meets the HL2 / 3.0mm grade requirements, which cannot meet the application scenarios that pay close attention to human life safety, such as the interior of train compartments, indoor environments, etc.; and the existing smoke suppressants contain a high proportion of magnesium hydroxide, which has a great impact on the mechanical properties, and the processing process easily decomposes crystal water, further reducing the mechanical properties of the product. Summary of the invention
[0004] The object of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a nylon material having excellent mechanical properties and flame retardant properties, and low smoke density, which can meet the HL3 / 3.0mm grade requirements of the EN45545-2:2020R22&R23 smoke density test, and a preparation method and application thereof.
[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a nylon composite material, the nylon composite material comprising the following components in parts by weight: 33-62 parts of polyamide resin, 13-42 parts of glass fiber, 12-26 parts of halogen-free flame retardant, 0.2-1.3 parts of zinc stannate, 0.8-5.2 parts of carbonate, and 0-3.2 parts of additive;
[0006] The thermal decomposition temperature of the carbonate is ≥480°C.
[0007] The nylon composite material provided by the present invention is compounded by selecting components in appropriate mass parts, especially adding appropriate mass parts of zinc stannate and carbonate within a specific thermal decomposition temperature range. On the one hand, the addition of carbonate within the specific thermal decomposition temperature range can reduce the addition amount of zinc stannate, thereby saving costs; on the other hand, the addition of carbonate within the specific thermal decomposition temperature range can achieve an excellent compounding effect with zinc stannate without damaging the mechanical properties of the nylon composite material, and greatly reduce the smoke density during combustion while having flame retardancy.
[0008] Specifically, during the combustion process, zinc stannate can make the main structure of the matrix material more stable, promote the formation of a carbon layer, and reduce the volatilization of combustibles. At the same time, tin is released in the gas phase and combines with free radicals to inhibit the formation of flames. Zinc mainly plays a role in the condensation flame retardant mechanism, catalyzing and promoting the decomposed polymer to char, improving the quality of the carbon layer, and further reducing the generation of smoke. Due to the high cost of zinc stannate, the present invention has found that by introducing carbonates, it can be well compounded with zinc stannate in the system, while reducing the amount of zinc stannate added without affecting the original performance of the material; the reason may be that the added carbonate with a thermal decomposition temperature within a specific range can decompose and produce carbon dioxide and corresponding oxides during the combustion process, and carbon dioxide plays a role in diluting the concentration of combustible gases and diluting smoke, reducing the release of toxic gases, and the corresponding oxides can cover the surface of the material to play a condensation phase synergistic flame retardant effect. This decomposition process will absorb a large amount of heat, reduce the surface temperature of the material, and promote the carbonization effect on the surface of the material. The dense carbon layer blocks the entry of external oxygen while also reducing the release of internal gas and slowing down the combustion rate. The combination of the two can effectively play a synergistic role; an excellent effect of reducing smoke density is achieved.
[0009] The thermal decomposition temperature of the carbonate is obtained by the ISO 11358-1:2022 standard TGA test.
[0010] Based on the total mass of the nylon composite material, the mass percentage of the polyamide resin is ≥29%.
[0011] Preferably, based on the total mass of the nylon composite material, the mass percentage of the polyamide resin is 45-60%.
[0012] For example, the mass fraction of the polyamide resin may be any point value or any range value between 33 and 62 parts, such as 35 to 60 parts, or 33, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62 parts, etc.; the mass fraction of the glass fiber may be any point value or any range value between 13 and 42 parts, such as 15 to 40 parts, or 13, 15, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 55, 58, 5 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, etc.; the halogen-free flame retardant can be any point value between 12-26 parts or any two point range values, such as 15-25 parts, or 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, etc.; the zinc stannate can be any point value between 0.3-1.2 parts or any two point range values, such as The carbonate may be any point value or any two point range values between 0.8-5.2 parts, for example, 1.0-5.0 parts, or 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3.0 parts, 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 3.0 parts, 3.0 parts, 3.2 ... .2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5.0 parts, 5.2 parts, etc.; the auxiliary agent can be any point value or any two point range values between 0-3.2 parts, for example, it can be 1.0-3.0 parts, or it can be 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3.0 parts, 3.2 parts, etc.
[0013] Preferably, in the nylon composite material, the mass percentage of carbonate is 0.5-8.1%.
[0014] As a preferred embodiment of the nylon composite material of the present invention, the mass ratio of the zinc stannate to the carbonate is 1:(1.0-8.5).
[0015] Exemplarily, the mass ratio of the zinc stannate to the carbonate may be any point value or any two point range value between 1:(1.0-8.5), such as 1:(1.3-8.3), or may be 1:1.0, 1:1.8, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6.0, 1:6.5, 1:7.0, 1:7.5, 1:8.0, 1:8.5, etc.
[0016] The present invention has found that the mass ratio of zinc stannate to carbonate affects the smoke density and mechanical properties of the product. When the mass ratio of the two is further selected to be within the above range, the comprehensive performance of the obtained product is better.
[0017] As a preferred embodiment of the nylon composite material of the present invention, the thermal decomposition temperature of the carbonate is 800-1340°C.
[0018] Exemplarily, the thermal decomposition temperature of the carbonate may be any point value or any two points in the range of 800-1340°C, such as 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1340°C, etc.
[0019] The present invention has found that the thermal decomposition temperature of carbonate not only affects the smoke density of the product, but also has a great influence on the mechanical properties of the product. When the thermal decomposition temperature of carbonate is further selected to be within the above range, the obtained product has better mechanical properties and lower smoke density.
[0020] Preferably, the carbonate includes at least one of strontium carbonate, calcium carbonate, magnesium carbonate and barium carbonate.
[0021] More preferably, the carbonate includes at least one of strontium carbonate and calcium carbonate.
[0022] When the carbonate is further selected as the above type, during the combustion process, the corresponding oxides formed by the decomposition of the carbonate cover the surface of the material and can better cooperate with zinc stannate to exert the condensation flame retardant effect, thereby better reducing the smoke density.
[0023] As a preferred embodiment of the nylon composite material of the present invention, the halogen-free flame retardant includes at least one of diethyl phosphinate, melamine polyphosphate, zinc borate, red phosphorus, organic hypophosphite, and phosphite.
[0024] As a preferred embodiment of the nylon composite material of the present invention, the halogen-free flame retardant includes diethyl phosphinate, melamine polyphosphate and zinc borate, and the mass ratio of diethyl phosphinate, melamine polyphosphate and zinc borate is diethyl phosphinate: melamine polyphosphate: zinc borate = (5-7): (0.8-1.2): (0.4-0.6).
[0025] Exemplarily, the mass ratio of the diethylphosphinate, melamine polyphosphate and zinc borate can be any point value or any two point range values between diethylphosphinate:melamine polyphosphate:zinc borate=(5-7):(0.8-1.2):(0.4-0.6), for example, it can be 5:0.8:0.4, 5:0.8:0.6, 5:1.0:0.4, 5:1.0:0.6, 6:0.8:0.4, 6:0.8:0.6, 6:1.0:0.4, 6:1.0:0.6, 7:0.8:0.4, 7:0.8:0.6, 7:1.0:0.4, 7:1.0:0.6, etc.
[0026] Exemplarily, the diethylphosphinate includes at least one of diethylaluminum phosphite, diethylzinc phosphite, and diethyltitanium phosphite.
[0027] As a preferred embodiment of the nylon composite material of the present invention, the polyamide resin includes at least one of PA66, PA6 and PA66 / 6T.
[0028] The present invention has no particular limitation on the type of polyamide resin, and conventional polyamide resins such as PA6, PA66, PA56, PA66 / 6T, MXD6, PA1012, PA11, PA12, PA1212, etc. are all applicable; however, when applied to at least one of PA66, PA6 and PA66 / 6T, the overall effect of the obtained product is better.
[0029] Preferably, the polyamide resin includes PA66 and PA6.
[0030] More preferably, the mass ratio of PA66 to PA6 is (40-50):(5-15).
[0031] As a preferred embodiment of the nylon composite material of the present invention, the relative resin viscosity of the polyamide resin is 1.8-2.8.
[0032] The relative resin viscosity of the polyamide resin is obtained by testing with reference to ISO 307:2007.
[0033] Exemplarily, the relative resin viscosity of the polyamide resin may be any point value or any two point range values between 1.8 and 2.8, such as 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, etc.
[0034] The present invention has found that when the relative resin viscosity of the polyamide resin is further selected to be 1.8-2.8, better processing performance can be achieved, thereby helping to achieve good product performance.
[0035] As a preferred embodiment of the nylon composite material of the present invention, the glass fiber is alkali-free and arsenic-free chopped glass fiber, the length of the glass fiber is 3.0-4.5 mm, and the average diameter is 8-10 μm.
[0036] The present invention has no particular requirements on the type, length and average diameter of the glass fiber, and the effects of the present invention can be achieved within the above ranges.
[0037] As a preferred embodiment of the nylon composite material of the present invention, the auxiliary agent includes at least one of an antioxidant and a lubricant.
[0038] Exemplarily, the antioxidant includes at least one of hindered phenol antioxidants, hindered amine antioxidants, thioester antioxidants, phosphite antioxidants, and inorganic phosphate antioxidants.
[0039] Exemplarily, the lubricant includes at least one of silicone masterbatch, polyethylene wax, stearate, and ethylene bis fatty acid amide.
[0040] In the second aspect of the present invention, the present invention also provides a method for preparing the nylon composite material, which comprises the following steps: weighing the dried raw materials and mixing them, and feeding them into a twin-screw extruder, extruding, drawing, cooling, pelletizing, and drying to obtain the nylon composite material.
[0041] Preferably, the method for preparing the nylon composite material comprises the following steps:
[0042] (1) adding an antioxidant, a lubricant, zinc stannate and a polyamide resin into a high speed mixer and mixing for 3-5 minutes to obtain component A;
[0043] (2) Add the halogen-free flame retardant and carbonate into a high-speed mixer and mix for 3-5 minutes to obtain component B;
[0044] (3) Component A is added to the main feeding system of a twin-screw extruder, and component B and glass fiber are added to the double-side feeding systems of the twin-screw extruder respectively, melt blended, extruded into pellets, and then cooled, pelletized, and dried to obtain a nylon composite material.
[0045] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: the aspect ratio of the twin-screw extruder is (36-48):1, the screw speed is 250-450rpm, and the extrusion temperature is 220-300°C.
[0046] In the third aspect of the present invention, the present invention also provides the use of the nylon composite material in the preparation of rail transportation, new energy and low-voltage electrical materials.
[0047] For example, nylon composite materials are used in the preparation of high-voltage connectors, industrial connectors, circuit breaker housings, switches and other materials.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The nylon composite material provided by the present invention is compounded by selecting components in appropriate mass parts, especially adding appropriate mass parts of zinc stannate and carbonate within a specific thermal decomposition temperature range, so that the obtained product has flame retardancy, significantly reduced smoke density, and excellent mechanical properties; specifically, the obtained nylon composite material has a tensile strength of more than 114MPa, a flexural strength of more than 195MPa, and an Izod notched impact strength of 8.6KJ / m 2 Above, smoke density is 109mg / cm 3 In the following, the flame retardancy level is V-0 level; and the preparation method of the composite material provided by the present invention is simple, which is conducive to actual production. DETAILED DESCRIPTION
[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0051] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0052] Polyamide 1: PA66, PA66 U3600 NC01, relative resin viscosity 2.4, INVISTA;
[0053] Polyamide 2: PA6, HY-2500A, relative resin viscosity 2.5, Haiyang Chemical Fiber;
[0054] Polyamide 3: PA66 / 6T, NPD-652, relative resin viscosity 2.4, INVISTA;
[0055] Glass fiber: ECS10-03-568H, length 3 mm, average diameter 10 μm, Jushi Group;
[0056] Halogen-free flame retardant 1: a compound of aluminum diethylphosphinate, melamine phosphate and zinc borate, wherein the mass ratio of aluminum diethylphosphinate, melamine phosphate and zinc borate is 6:1:0.5, aluminum diethylphosphinate is purchased from Exoplit OP1230 of Clariant, and melamine phosphate and zinc borate are commercially available products;
[0057] Halogen-free flame retardant 2: a compound of aluminum diethylphosphinate, melamine phosphate and zinc borate, wherein the mass ratio of aluminum diethylphosphinate, melamine phosphate and zinc borate is 3:1.2:0.6, aluminum diethylphosphinate is purchased from Exoplit OP1230 of Clariant, and melamine phosphate and zinc borate are commercially available products;
[0058] Halogen-free flame retardant 3: red phosphorus masterbatch, FR9950T, Tongcheng Xinde New Materials Co., Ltd.
[0059] Zinc stannate: commercially available;
[0060] Magnesium carbonate: thermal decomposition temperature is 500°C, commercially available;
[0061] Calcium carbonate: thermal decomposition temperature is 800°C, commercially available;
[0062] Strontium carbonate: thermal decomposition temperature is 1340°C, commercially available;
[0063] Barium carbonate: thermal decomposition temperature is 1450°C, commercially available;
[0064] Zinc carbonate: thermal decomposition temperature is 330°C, commercially available;
[0065] Antioxidant: a mixture of IRGANOX 1098 and Revonox 608 in a mass ratio of 1:1, commercially available;
[0066] Lubricant: montan ester, commercially available.
[0067] The glass fibers, antioxidants and lubricants used in the parallel experiments of the embodiments and comparative examples were kept consistent.
[0068] Examples 1-14 and Comparative Examples 1-5
[0069] The present invention provides a nylon composite material according to the embodiment and comparative example. The component contents (parts by weight) of the nylon composite material are shown in Table 1-3.
[0070] Table 1
[0071]
[0072] Table 2
[0073] Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Polyamide 1 55 55 55 55 55 Fiberglass 25 25 25 25 25 Halogen-free flame retardant 1 / / 16 16 16 Halogen-free flame retardant 2 16 / / / / Halogen-free flame retardant 3 / 16 / / / Zinc stannate 0.8 0.8 0.8 0.8 0.8 Magnesium carbonate 2 2 / / / Calcium carbonate / / 2 / / Strontium carbonate / / / 2 / Barium carbonate / / / / 2 Antioxidants 0.4 0.4 0.4 0.4 0.4 Lubricants 0.5 0.5 0.5 0.5 0.5
[0074] Table 3
[0075]
[0076]
[0077] The preparation method of the nylon composite material provided in Example 1 is:
[0078] (1) adding an antioxidant, a lubricant, zinc stannate and a polyamide resin into a high-speed mixer and mixing for 4 minutes to obtain component A;
[0079] (2) adding the halogen-free flame retardant and carbonate into a high-speed mixer and mixing for 4 minutes to obtain component B;
[0080] (3) adding component A to the main feeding system of a twin-screw extruder, and adding component B and glass fiber to the double-side feeding systems of the twin-screw extruder respectively, melt blending, extruding and granulating, and then cooling, pelletizing and drying to obtain a nylon composite material;
[0081] The parameters of the twin-screw extruder are as follows: the aspect ratio of the twin-screw extruder is 42:1, the screw speed is 350 rpm, and the extrusion temperature is 220-300°C.
[0082] The preparation methods of the nylon composite materials provided in Examples 2-14 and Comparative Examples 1-5 are consistent with that in Example 1, except that no relevant components are added.
[0083] Effect example
[0084] The effect examples of the present invention verify the performance of the products prepared in the embodiments and comparative examples; the test items include the following aspects:
[0085] 1. Tensile strength: After the obtained nylon composite material was dried in an oven at 120°C for 4 hours, ISO standard tensile specimens were injection molded, and the tensile strength of the nylon composite material was tested according to ISO 527-2:2012 standard;
[0086] 2. Flexural strength: After the obtained nylon composite material was dried in an oven at 120°C for 4 hours, ISO standard bending specimens were injection molded, and the flexural strength of the nylon composite material was tested according to ISO 178:2019 standard;
[0087] 3. Izod notched impact strength: After the obtained nylon composite material was dried in an oven at 120°C for 4 hours, an ISO standard Izod notched impact specimen was injection molded, and the Izod notched impact strength of the nylon composite material was tested according to ISO 180:2019 standard;
[0088] 4. UL94 vertical burning @1.6mm: After the obtained nylon composite material was dried in an oven at 120°C for 4 hours, 1.6mm thick UL flame retardant specimens were injection molded to test the flame retardant properties of the nylon composite material according to the UL94 standard;
[0089] 5. Smoke density test @3.0mm: After drying the obtained nylon composite material in an oven at 120℃ for 4 hours, an ISO standard 3.0mm smoke density test specimen was injection molded. The smoke density data of the nylon composite material was tested according to ISO 5659-2:2017 standard. The test conditions were: irradiation intensity 25kW / m 2 , duration 10min;
[0090] The test results are shown in Table 4;
[0091] Table 4
[0092]
[0093] It can be seen from Table 4 that when the technical solution of the present invention is adopted, the obtained product has excellent flame retardancy and mechanical properties, and low smoke density; specifically, the obtained nylon composite material has a tensile strength of more than 114 MPa, a flexural strength of more than 195 MPa, and an Izod notched impact strength of 8.6 KJ / m 2 Above, smoke density is 109mg / cm 3 The following flame retardant grades are all V-0;
[0094] It can be seen from Examples 1-5 and Comparative Examples 3-4 that the mass fraction of the components and the mass ratio between the components will affect the performance of the product. When the amount of carbonate added in Comparative Example 3 is too much, the mechanical properties of the obtained product are low; when the amount of carbonate added in Comparative Example 4 is too little, the obtained product cannot achieve effective reduction in smoke density;
[0095] It can be seen from Example 1 and Examples 6-9, and Example 1 and Examples 10-11 that when the types of polyamide and halogen-free flame retardant are further selected as the preferred ones of the present invention, the comprehensive performance of the obtained product is better;
[0096] It can be seen from Example 1, Examples 12-14 and Comparative Example 5 that the type of carbonate affects the comprehensive performance of the product. When the thermal decomposition temperature of the carbonate selected in Comparative Example 5 is not within the range given in the present invention, the obtained product cannot exert the synergistic effect of carbonate and zinc stannate, and cannot achieve the reduction of smoke density;
[0097] It can be seen from Example 1 and Comparative Examples 1-2 that zinc stannate and carbonate have a compounding effect. When zinc stannate is not added in Comparative Example 1, the smoke density of the obtained product cannot be lower than 150. When carbonate is not added in Comparative Example 2, the smoke density of the obtained product is also limited.
[0098] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A nylon composite material, characterized in that: The nylon composite material comprises the following components in parts by weight: 33-62 parts of polyamide resin, 13-42 parts of glass fiber, 12-26 parts of halogen-free flame retardant, 0.2-1.3 parts of zinc stannate, 0.8-5.2 parts of carbonate, 0-3.2 parts of additives; The thermal decomposition temperature of the carbonate is ≥480°C.
2. The nylon composite material according to claim 1, characterized in that: The mass ratio of the zinc stannate to the carbonate is 1:(1.0-8.5).
3. The nylon composite material according to claim 1, characterized in that: The thermal decomposition temperature of the carbonate is 800-1340°C.
4. The nylon composite material according to claim 1, characterized in that: The halogen-free flame retardant includes at least one of diethyl phosphinate, melamine polyphosphate, zinc borate, red phosphorus, organic hypophosphite and phosphite.
5. The nylon composite material according to claim 4, characterized in that: The halogen-free flame retardant comprises diethyl phosphinate, melamine polyphosphate and zinc borate, wherein the mass ratio of diethyl phosphinate, melamine polyphosphate and zinc borate is diethyl phosphinate: melamine polyphosphate: zinc borate = (5-7): (0.8-1.2): (0.4-0.6).
6. The nylon composite material according to claim 1, characterized in that: The polyamide resin includes at least one of PA66, PA6 and PA66 / 6T; preferably, the polyamide resin includes PA66 and PA6; more preferably, the mass ratio of PA66 to PA6 is (40-50):(5-15).
7. The nylon composite material according to claim 1, characterized in that: The carbonate includes at least one of strontium carbonate, calcium carbonate, magnesium carbonate and barium carbonate.
8. The nylon composite material according to claim 1, characterized in that: The auxiliary agent includes at least one of an antioxidant and a lubricant.
9. The method for preparing the nylon composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, and performing extrusion, strip drawing, cooling, pelletizing and drying to obtain a nylon composite material.
10. Use of the nylon composite material according to any one of claims 1 to 8 in the preparation of rail transportation, new energy and low-voltage electrical materials.
Citation Information
Patent Citations
Stannate flame-retardant nylon and method for preparing same
CN109438977A
Low-mold-scale halogen-free flame-retardant thermoplastic polyamide composition as well as preparation method and application thereof
CN112409786A
Special nylon composite material for green and environment-friendly halogen-free flame-retardant ribbon and preparation method of special nylon composite material
CN115746553A
Aqueous zinc-polyamide complex solution
US5587147A
Cited By
Nylon composite material as well as preparation method and application thereof
CN119978792A